SANKSI PIDANA TINDAK PIDANA PENGANIAYAAN DENGAN RENCANA TERLEBIH DAHULU (PUTUSAN NO. 209/PID.B/2021/PN.JKT.BRT) - Clara Ayuningtyas Paramitha; Vience Ratna Multiwijaya (Reformasi Hukum Trisakti, 2022)
The defendant, Abdul Jabar bin Iyep Efendi, committed the act of assault that resulted in the victim's serious injury, which was committed by abusing the victim by using a wrench on the victim's head. This action constitutes the criminal sanction for the crime of maltreatment with prior planning. The issue is whether the perpetrators of the crime of persecution with prior planning comply with Article 351, Paragraph 2 of the Criminal Code (Decision Number 209/Pid.B/2021/PN.Jkt.Brt), and whether the punishment in Decision Number 209/Pid.B/2021/PN.Jkt.Brt is consistent with the intended sentence. The data source is secondary, and the study method is normative and descriptive-analytical in character. Secondary data are used as the data source, and deductive reasoning is used to draw conclusions while conducting qualitative data analysis and literature reviews. The findings of the study, the discussion, and the conclusion show that the perpetrator's actions do not fit the criteria in Article 351, paragraph 2, of the Criminal Code because they involved premeditation on their part, and the judge's sentence for the defendant fits the criteria for punishment, namely 3R and 1D.